Resting-state functional MRI in depression unmasks increased connectivity between networks via the dorsal nexus - Sheline, Yvette I.; Price, Joseph L.; Yan, Zhizi; Mintun, Mark A.; Raichle, Marcus E. (Proceedings of the National Academy of Sciences - PNAS, 2010)
To better understand intrinsic brain connections in major depression, we used a neuroimaging technique that measures resting state functional connectivity using functional MRI (fMRI). Three different brain networks—the cognitive control network, default mode network, and affective network—were investigated. Compared with controls, in depressed subjects each of these three networks had increased connectivity to the same bilateral dorsal medial prefrontal cortex region, an area that we term the dorsal nexus. The dorsal nexus demonstrated dramatically increased depression-associated fMRI connectivity with large portions of each of the three networks. The discovery that these regions are linked together through the dorsal nexus provides a potential mechanism to explain how symptoms of major depression thought to arise in distinct networks—decreased ability to focus on cognitive tasks, rumination, excessive self-focus, increased vigilance, and emotional, visceral, and autonomic dysregulation—could occur concurrently and behave synergistically. It suggests that the newly identified dorsal nexus plays a critical role in depressive symptomatology, in effect "hot wiring" networks together; it further suggests that reducing increased connectivity of the dorsal nexus presents a potential therapeutic target.